2015
DOI: 10.1371/currents.dis.62e9286d152de04799644dcca47d9288
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Describing the Impact of Cyclone, Storm and Flood Related Disasters on Treatment Management, Care and Exacerbations of Non-communicable Diseases and the Implications for Public Health

Abstract: Introduction: Over the last quarter of a century the frequency of natural disasters and the burden of non-communicable diseases (NCD) across the globe have been increasing. For individuals susceptible to, or chronically experiencing, NCDs this has become a significant risk. Disasters jeopardize access to essential treatment, care, equipment, water and food, which can result in an exacerbation of existing conditions or even preventable death. Consequently, there is a need to expand the public health focus of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 61 publications
2
62
0
Order By: Relevance
“…Natural disasters are increasing in frequency ( 1 – 3 ). Growing research has shown an association between natural disasters and mental health problems ( 4 8 ).…”
mentioning
confidence: 99%
“…Natural disasters are increasing in frequency ( 1 – 3 ). Growing research has shown an association between natural disasters and mental health problems ( 4 8 ).…”
mentioning
confidence: 99%
“…Respiratory symptoms (16) General symptoms (25) General symptoms (+13) General symptoms (12) Respiratory symptoms (19) Hypertension (+11) Heart failure (10) Hypertension (15) Myocardial infarction (+8) Sepsis (7) Heart failure (13) Hypertensive kidney disease (+8) Cellulitis or abscess (7) Myocardial infarction (12) Chronic bronchitis (+8) Urinary tract infection (7) Chronic bronchitis (12) Chronic kidney disease (+7) Asthma (7) Asthma (12) Prescription refills (+7) Abdominal/pelvic symptoms (6) Hypertensive kidney disease (10) Drug dependence (+7) Cardiac dysrhythmias (5) Sepsis (9) Dialysis dependence (+6) Ischemic heart disease (5) Ischemic heart disease (9) Electrolyte disorder (+6) Diagnoses in bold highlight the differences in categories before and after Hurricane Sandy's landfall. Post-procedural aftercare (17) Post-procedural aftercare (+11) Post-procedural aftercare (6) Chronic skin ulcer (14) Chronic skin ulcer (+9) Electrolyte disorder (6) Electrolyte disorder (13) Electrolyte disorder (+7) Ischemic heart disease (5) Hyperlipidemia (11) Post-procedural state (+7) Chronic skin ulcer (5) Post-procedural state (10) Overweight or obese (+5) Chronic kidney disease (4) Ischemic heart disease (10) Ischemic heart disease (+5) Hypertensive kidney disease (4) Drug abuse (8) Cardiac dysrhythmia (+4) Drug abuse (4) Chronic kidney disease (7) Chronic airway obstruction (+4) Other health hazards (7) Overweight or obese (7) Osteomyelitis (+4) Diagnoses in bold highlight the differences in categories before and after Hurricane Sandy's landfall.…”
Section: Highest Increases Before and Aftermentioning
confidence: 99%
“…Post-procedural aftercare (17) Post-procedural aftercare (+11) Post-procedural aftercare (6) Chronic skin ulcer (14) Chronic skin ulcer (+9) Electrolyte disorder (6) Electrolyte disorder (13) Electrolyte disorder (+7) Ischemic heart disease (5) Hyperlipidemia (11) Post-procedural state (+7) Chronic skin ulcer (5) Post-procedural state (10) Overweight or obese (+5) Chronic kidney disease (4) Ischemic heart disease (10) Ischemic heart disease (+5) Hypertensive kidney disease (4) Drug abuse (8) Cardiac dysrhythmia (+4) Drug abuse (4) Chronic kidney disease (7) Chronic airway obstruction (+4) Other health hazards (7) Overweight or obese (7) Osteomyelitis (+4) Diagnoses in bold highlight the differences in categories before and after Hurricane Sandy's landfall. ED, emergency department.…”
Section: Highest Increases Before and Aftermentioning
confidence: 99%
“…An earlier review of 48 published studies found natural disasters like cyclone, flood and storm impact on treatment management and care of people with Non Communicable Diseases (NCDs), with exacerbation of illness, complications or even death. 10 During post hurricane Katrina in the USA, availability of transportation affected access to cancer care in patients with early stage cancer. 11 We fear that a similar situation is likely as a result of the current natural crisis in Nepal.…”
Section: Cancer At the Time Of Nepal's Earthquakes Aftermathmentioning
confidence: 99%
“…Besides that, in line with the Sendai Framework for Disaster Risk Reduction (2015-2030), the traditional disaster approaches for 'building back better" needs to incorporate NCDs like cancer with understanding of direct and indirect (preventable) factors that exacerbate them during and after the disasters, to retain and restore health of people. 10 Healthy people are resilient, and quickly recover from emergencies and disaster like earthquakes. 17 So, it is imperative to Nepal's sustainable recovery and resilience to have disaster rebuilding, reconstruction and rehabilitation go hand in hand with health system-strengthening, building of population based registry to deal a menace of NCDs like cancer.…”
Section: Cancer At the Time Of Nepal's Earthquakes Aftermathmentioning
confidence: 99%